1500. Population-based incidence, health care resource utilization and cost among children < 5 years of age hospitalized with RSV, Utah. (31st December 2020) - Ampofo, Krow; Choi, Yoonyoung; Heller, Evan G; Platt-Koch, Alexander G; Gesteland, Per H; Adua, Lazarus; Finelli, Lyn
Abstract: Background: Respiratory Syncytial Virus (RSV) is one of the most common causes of childhood lower respiratory tract infection (LRTI) worldwide. Accurate data are critical to inform the rationale for RSV vaccine and immunoprophylaxis development. We evaluated the burden of laboratory-confirmed RSV from hospitalized children. Methods: During the 2019-2020 RSV season, we prospectively identified children < 5 years of age hospitalized with laboratory-confirmed RSV LRTI at Primary Children's and Riverton hospitals in Salt Lake City, Utah. Outcomes included Salt Lake county RSV hospitalization rates, adjusted for market share, health care resource utilization including intensive care unit (ICU) stays, mechanical ventilation, length of stay (LOS), and total hospital costs. Results: A total of 284 children had laboratory-confirmed RSV LRTI hospitalizations during the 2019-2020 RSV season: 106 (37%) < 6 months of age; 67 (24%) had high-risk medical conditions (HMC); 70 (25%) children had an ICU stay; 18 (6%) required mechanical ventilation; 132 (46%) received antibiotics and median hospital LOS of 2.3 days (IQR 1.6- 3.6). Population-based incidence rates of RSV hospitalization were 4.6/1000 (range 0.7/1000 to 17/1000). The highest rates were in children < 6 months, and rates decreased with increasing age. The mean hospital cost was 12, 974.6 (standard deviation: 19869.7), with a total for the cohort was 3.7 million; 42% was accounted for by children < 6 months. Median age of children with HMC's were significantly older (18.7 mon vs. 12.7 mon; p=0.001) than healthy, but comparable mean hospital cost (14208.5 vs. 12593.2) and median hospital LOS (2.4 vs. 2.3). Conclusion: Hospitalized RSV LRTI among children < 5 years remains significant, and is associated with substantial HCRU, antibiotic use and morbidity. Nationwide, the mean hospital costs may total 1.1 billion. Our data support the need for RSV vaccines and immunoprophylaxis to prevent RSV hospitalization. Disclosures: Krow Ampofo, MBChB, Merck (Grant/Research Support) Yoonyoung Choi, PhD, MS, RPh, Merck (Employee) Lyn Finelli, DrPH, MS, Merck & Co Inc, (Employee)